Generation of synthetic antibody fragments with optimal complementarity determining region lengths for Notch-1 recognition - Maruthachalam, Bharathikumar Vellalore; Barreto, Kris; Hogan, Daniel; Kusalik, Anthony; Geyer, Clarence Ronald (Frontiers in Microbiology, 2022)
Synthetic antibodies have been engineered against a wide variety of antigens with desirable biophysical, biochemical, and pharmacological properties. Here, we used synthetic antibody technology to generate antigen-binding fragments (Fabs) against Notch-1. Two single-framework synthetic Fab libraries, named S and F, were screened against the recombinant human Notch-1 extracellular domain using phage display. Both libraries were built on a modified trastuzumab framework, containing two or four diversified complementarity-determining regions (CDRs). We showed that screening focused diversity libraries, implementing next-generation sequencing (NGS) approaches, fine-tuning the CDR length diversity, and making small changes to diversity designs provided improved binding solutions for Notch-1 recognition. These findings have implications for antibody library design and antibody phage display. In total, we generated twelve Notch-1 Fabs with ten different CDRH3 lengths. These Fabs possessed high affinity for Notch-1 (sub-nM to mid-nM KD,app values) and exhibited different binding specificities against Notch-2, Notch-3, Jagged-1, and Jagged-2. The highest-affinity Fab bound to Notch-1 with a KD,app value of 0.15 ± 0.01 nM and was specific for Notch-1.